Satu Metode Istinbaṭ dalam Hukum Qauli dan Ilḥaqi pada Baḥtsul Masaʾil Nahdlatul Ulama: Dialektika Tradisi, Rasionalitas, dan Relevansi - Nurhuda, Abid; Azhar , Aurizan Himmi; Inas , Balqis; Asparina, Atropal; Rahim , Yusuf; Ansori, Inamul Hasan (LPPM UNHASY, 2025)
The Baḥtsul Masaʾil tradition within Nahdlatul Ulama (NU) is an epistemological laboratory that links the authenticity of classical fiqh tradition with the social dynamics of Indonesian society. In this tradition, the istinbaṭ al-ḥukm method used is based on two main approaches: qauli and ilḥaqi. This article aims to examine in depth the epistemological, methodological, and contextual relevance of these two approaches in responding to modern Islamic legal problems. Using the analytical framework of uṣul al-fiqh and maqaṣid al-shariʿah, this study explains that the qauli approach functions to maintain the authority of the sanad of knowledge by strengthening the legitimacy of the school of thought texts, while the ilḥaqi approach opens up innovative space through social analogies and rational reasoning based on legal similarities. The findings show that the integration of the two produces a contextual, participatory, and humanistic model of ijtihad jama'i. In the contemporary context, NU's istinbaṭ method has proven adaptive to issues such as fintech, bioethics, and national legal plurality. Thus, Baḥtsul Masaʾil is not merely a traditional fatwa forum, but rather a dialectical space for Islamic law that revitalizes classical fiqh reasoning in the modern social landscape.